PUPUK Bayfolan DAN PUPUK KANDANG SAPI BERPENGARUH KEPADA PERTUMBUHANDAN PRODUKSI KACANG PANJANG (Vigna Sinensis L.) - Dartius ,; Alridiwirsah ,; Eko Saputra Sinaga (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
AbstractThis study aims to determine the growth and production of long beans (Vigna sinensis L) on the provision of bayfolan fertilizer and manure cow. The design used was Randomized Design Group factorial with two factors were studied, namely: Fertilizer Bayfolan factor which is denoted by the letter